Comprehensive investigation of flood-resilient neighborhoods: the case of Adama City, Ethiopia - Bikila Merga Leta; Dagnachew Adugna; Alazar Assefa Wondim (Applied Water Science, 2024)
Abstract Adama is the second most populous city in Ethiopia and experiences frequent flash floods that have a detrimental impact on the community’s livelihood. To this effect, this study emphasizes the significance of conducting a comprehensive investigation to identify flood-resilient neighborhoods in Adama City. By considering the existing spatial pattern and morphology that are resilient to urban flooding, the city can enhance its flood management strategies in the future. The findings of this study demonstrate varying levels of spatial connectivity within Adama City. Detailed examination of two neighborhoods identified through space syntax analysis with high and low spatial connectivity revealed important insights into flood resilience. The high-connective neighborhoods exhibited well-interconnected street systems with manageable street spacing, facilitating efficient runoff flow and effective flood management during flooding events. These neighborhoods also had shorter block sizes with frequent intersections, promoting better water drainage and reducing the risk of flooding during heavy rain events. The grid pattern observed in these areas allowed for efficient water runoff through multiple drainage paths, including the street surfaces. On the contrary, neighborhoods with low spatial connectivity exacerbated urban flooding. The lack of connectivity and abundance of dead-end streets posed challenges for flood evacuation during emergencies. Irregular block arrangements disrupted the natural drainage system, aggravating the potential for urban flooding. These findings have implications for other flood-prone areas of neighborhoods in Adama City and similar urban areas in the global south on how human settlements are arranged spatially to mitigate urban flood vulnerability.